2020
DOI: 10.1155/2020/8956504
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunctions May Be One of the Major Causative Factors Underlying Detrimental Effects of Benzalkonium Chloride

Abstract: Benzalkonium chloride (BAC) is currently the most commonly used antimicrobial preservative in ophthalmic solutions, nasal sprays, and cosmetics. However, a large number of clinical and experimental investigations showed that the topical administration of BAC-containing eye drops could cause a variety of ocular surface changes, from ocular discomfort to potential risk for future glaucoma surgery. BAC-containing albuterol may increase the risk of albuterol-related systemic adverse effects. BAC, commonly present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 89 publications
(103 reference statements)
0
19
0
Order By: Relevance
“…In addition, the increased level of ROS affected the activity of LDH too (Figure 3b). This could be due to an increase of glycolysis rate versus Krebs cycle, consequent to a mitochondrial dysfunction induced by the exposure of fish to this cationic surfactant as previously was noticed [49,50].…”
Section: Discussionmentioning
confidence: 53%
“…In addition, the increased level of ROS affected the activity of LDH too (Figure 3b). This could be due to an increase of glycolysis rate versus Krebs cycle, consequent to a mitochondrial dysfunction induced by the exposure of fish to this cationic surfactant as previously was noticed [49,50].…”
Section: Discussionmentioning
confidence: 53%
“…It has been widely applied in treating a large number of pathologies related to oxidative stress [ 29 ]. Previously, we also showed that SkQ1 alleviated and even prevented prooxidant-induced oxidative stress in yeasts [ 77 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 98%
“…In contrast to cell cultures, they vigorously grow on a variety of simple, well-defined and inexpensive media, and respond quickly to various substances. Additionally, these giant cells normally contain freely moving mitochondria that are fragmented when oxidative stress is imposed [ 77 , 78 , 79 , 80 ]. If we add easy-to-visualize mitochondria in the cell and the possibility to explore a large number of individual cells using modern methods of flow cytometry and time-lapse microscopy, it becomes clear to us that D. magnusii cells are particularly suitable for revealing a cross-talk among oxidative stress, its propagation, and mitochondrial dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, the rescuing effect of BAC was via mitochondrial ATP synthesis inhibition due to its interference with mitochondrial respiratory complexes. Indeed, recently, it has been shown that BAC inhibits respiration and ATP production when added to intact mitochondria [ 24 ]. In agreement with this, we found that BAC induced an approximately 3-fold stimulation of the rate of glucose consumption ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%